Musical instrumentation among the San (Bushmen) of the Central Kalahari - Nurse, G. T. (International Library of African Music, 1972)
The author was fortunate enough to be able to spend some days among them in the company of Dr. Jiro Tanaka of Kyoto University, who was in the process of winding up his second extended period of fieldwork. This meant that not only was an expert interpreter on hand, but that unusually favourable opportunities of observing San musical life were provided by the eagerness of the people to show their appreciation of Dr. Tanaka. It was also possible to make some assessment of the nature and extent of the influence of outside musical styles on them. The results of the assessment have led to the use of the cumbersome term "instrumentation” in the tide of this paper. Of the six varieties of manufactured musical instrument encountered, only two appeared to be authentically San. Three of the other four incorporated worked metal in their construction, and though the G/wi now have the knowledge to work iron it is not sufficient for the production of the metal parts of their instruments. The two "native” instruments were constructed of locally available materials and produced sounds which were of so different a pitch and timbre from those of the metal-containing instruments that they could not be played at the same time. In addition, the use of hands and feet, and to a certain extent of the voice, was instrumental.
Keywords: Ethnomusicology; Music; Kalahari Desert; San (African people); Musical instruments; Africa; African Music